High-heat-resistance copper-clad plate and preparation process thereof
By pretreating the polyimide film and preparing modified silicone-containing resin and composite flame retardant materials, combined with the hot pressing curing process, the problem of insufficient heat resistance and flame retardant properties of the polyimide film at high welding temperatures is solved. It significantly improves the heat resistance and flame retardant properties of copper clad plates, meeting the safety and reliability requirements of high-temperature welding.
Patent Information
- Application Number
- CN202411854117.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing polyimide films have insufficient heat resistance and flame retardancy at high welding temperatures, and cannot meet the requirements of high temperature welding.
By pretreating the polyimide film, and preparing modified silicone-containing resin and composite flame retardant materials, combined with the hot pressing curing process, high heat-resistant copper clad plates were prepared. The modified silicone-containing resin forms a crosslinked structure through esterification reaction to improve heat resistance; the composite flame retardant material forms a stable chemical bond with traminol and phytic acid through the reaction of elotite nanotubes to improve flame retardant performance.
It significantly improves the heat resistance and flame retardant properties of copper clad plate, meets the safety and reliability requirements of high-temperature welding, and extends the service life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a high heat-resistant copper clad laminate and a preparation process thereof. Background Art
[0002] Copper clad laminate refers to a copper clad laminate material made of copper foil, adhesive and insulating film material. After subsequent welding, etching, punching and other process treatments, the prepared copper clad laminate is widely used in printed circuit boards in computers, mobile phones, medical and health equipment, aerospace and navigation fields. Copper clad laminates can be divided into rigid copper clad laminates and flexible copper clad laminates according to their mechanical rigidity. The film materials used for rigid copper clad laminates are mostly wood pulp paper, multi-layer glass fiber cloth, etc., while flexible copper clad laminates mostly use flexible films such as polyethylene terephthalate film, polyester imide film and polyimide film as reinforcement materials. Compared with rigid boards, flexible copper clad laminates have the characteristics of high wiring density, light weight and good bending properties, making them more and more widely used.
[0003] Although the existing polyimide film has the advantages of low heat shrinkage and good dimensional stability, its adhesion to copper foil is poor, and its heat resistance and flame retardancy are insufficient, and it cannot meet the requirements of high welding temperature.
[0004] Therefore, it is necessary to propose a high heat-resistant copper clad laminate with good flame retardancy and a preparation process thereof to meet high temperature welding requirements. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high heat-resistant copper-clad laminate and a preparation process thereof.
[0006] A preparation process of a high heat-resistant copper-clad laminate comprises the following steps: S1: Pretreatment of polyimide film The thermosetting polyimide film is placed in a 5% sodium hydroxide aqueous solution at 50-60° C., soaked for 3-5 minutes, taken out and dried to obtain a pretreated polyimide film; S2: Preparation of mixed glue solution The modified silicone-containing resin liquid, the modified adhesive liquid and the composite flame retardant material are stirred and mixed uniformly to obtain a mixed adhesive liquid; S3: Preparation of prepreg The mixed adhesive is applied to the surface of the pretreated polyimide film, and baked at 80-90°C and 130-150°C for 10-12h and 1-2h, respectively, to obtain a prepreg; S4: Hot Press Curing Several prepregs are stacked together, cut, and then covered with copper foil on one or both sides, and subjected to heat-pressing curing to obtain a high heat-resistant copper-clad laminate; The mixed adhesive solution includes, by weight: 20-30 parts of modified silicone resin solution, 45-55 parts of modified adhesive solution and 30-40 parts of composite flame retardant material; The raw material components required for the modified silicone-containing resin liquid include, by weight: 10-12 parts of isosorbide bis(terephthalate), 1-2 parts of bisphenol A, 16-20 parts of dibenzoate, 0.01-0.03 parts of 4-dimethylaminopyridine, 30-40 parts of silicone-containing resin and 55-75 parts of N,N-dimethylformamide; The raw material components required for the modified adhesive solution include, by weight: 16-20 parts of 2,4-toluene diisocyanate, 21-23 parts of isophorone diisocyanate, 34-42 parts of bisphenol A dianhydride, 45-50 parts of diphenyl ether dianhydride, 20-30 parts of terminal hydroxyl polydimethylsiloxane and 60-70 parts of N,N′-dimethylacetamide.
[0007] Furthermore, the preparation steps of the modified silicone-containing resin liquid are as follows: Add isosorbide bis(terephthalate), bisphenol A and dibenzoate into a reactor, heat and stir at 150-160° C. for 8-10 minutes to obtain a mixed reaction liquid; Add 4-dimethylaminopyridine to the mixed reaction liquid, continue heating at 150-160°C for 20-30 min, then raise the temperature to 180-190°C, distill under reduced pressure for 40-50 min to remove phenol, then raise the temperature to 250-270°C, and heat to react for 2-3 h to obtain a crude product; The crude product is dissolved in chloroform, and methanol is added for alcohol precipitation, and the modified agent is obtained by centrifugal separation, washing and drying; The above-mentioned modifier and silicon-containing resin are added to N,N-dimethylformamide, heated and stirred at 60-70° C. to fully dissolve, and then the N,N-dimethylformamide is removed by rotary evaporation to obtain a modified silicon-containing resin liquid.
[0008] Further, the preparation steps of the silicone-containing resin are as follows: Dissolve m-diethynylbenzene and methylphenyldichlorosilane in tetrahydrofuran at a solid-liquid ratio of 1 g: (20-30) mL to obtain a m-diethynylbenzene solution and a methylphenyldichlorosilane solution; The above m-diethynylbenzene solution was added to ethylmagnesium bromide, and the mixture was heated to reflux at 60-70°C for 2-3 hours under the protection of nitrogen, and then naturally cooled to room temperature to obtain intermediate A; Add the above-mentioned methylphenyldichlorosilane solution to the above-mentioned intermediate A, continue heating and reflux reaction at 60-70° C. for 2-3 hours, and naturally cool to room temperature to obtain intermediate B; The intermediate B is placed in an ice-water bath at 3-5°C, and acetic acid-toluene solution and hydrochloric acid aqueous solution are added, then transferred to a centrifuge for centrifugation, and the upper organic phase is separated and washed, and the solvent is removed by reduced pressure distillation to obtain a silicon-containing resin.
[0009] Further, the preparation steps of the modified glue solution are as follows: Add bisphenol A dianhydride and diphenyl ether dianhydride into N,N′-dimethylacetamide, heat and stir to mix at 70-80° C. and keep warm to obtain a mixed solution; Add 2,4-toluene diisocyanate and isophorone diisocyanate to the mixed solution, keep warm and stir for 1-2 hours, then raise the temperature to 110-120°C, continue stirring and reacting for 1-2 hours, and naturally cool to room temperature to obtain a matrix glue solution; Add terminal hydroxyl polydimethylsiloxane to the above-mentioned base adhesive solution, heat and stir at 60-80° C. for 2-4 hours, and naturally cool to room temperature to obtain a modified adhesive solution.
[0010] Furthermore, the preparation steps of the composite flame retardant material are as follows: S3.1: Add tromethamine to 70% ethanol solution at a solid-liquid ratio of 1 g: (10-12) mL, heat and stir at 60-70°C until completely dissolved, to obtain a tromethamine solution; S3.2: Adding halloysite nanotubes to the above-mentioned tromethamine solution at a solid-liquid ratio of 1 g: (30-40) mL, ultrasonically treating for 30-40 min, and uniformly dispersing to obtain a halloysite nanotube dispersion; S3.3: Add phytic acid to the above-mentioned halloysite nanotube dispersion, heat and stir at 60-80° C. for 2-4 hours, and after centrifugal separation, wash and dry the precipitate to obtain a composite flame retardant material.
[0011] Furthermore, the volume ratio of ethylmagnesium bromide, m-diethynylbenzene solution and methylphenyldichlorosilane solution is 1:(1.8-2.2):(1.9-2.3).
[0012] Furthermore, the acetic acid-toluene solution is prepared by mixing acetic acid and toluene in a volume ratio of 1:(4-6), and the molar ratio of acetic acid to m-diethynylbenzene is (2-3):1.
[0013] Furthermore, the concentration of the hydrochloric acid aqueous solution is 10%, and the volume ratio of the hydrochloric acid aqueous solution to the acetic acid-toluene solution is 1:(3-5).
[0014] Furthermore, the molar ratio of phytic acid to tromethamine is 1:(1.1-1.3).
[0015] A high heat-resistant copper-clad laminate is prepared by any of the above-mentioned processes for preparing a high heat-resistant copper-clad laminate.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention first uses m-diethynylbenzene and methylphenyldichlorosilane as raw materials to react and prepare a silicon-containing resin, and then uses isosorbide bis(terephthalate), bisphenol A and dibenzoate as raw materials to react and prepare a modifier under the catalysis of 4-dimethylaminopyridine. When the modifier is used to modify the silicon-containing resin to prepare a modified silicon-containing resin, the isosorbide bis(terephthalate), bisphenol A and dibenzoate in the modifier form a complex cross-linking structure through an esterification reaction, thereby increasing the glass transition temperature of the silicon-containing resin. The ester bond and cross-linking structure in the modifier can reduce the thermal decomposition of the silicon-containing resin at high temperatures, and the benzene ring and ester group in the modifier can improve the thermal conductivity of the silicon-containing resin, which is conducive to the uniform distribution of heat and further improves the heat resistance of the silicon-containing resin. Therefore, after the modified silicon-containing resin is added to the modified adhesive, the heat resistance of the modified adhesive can be effectively improved, thereby achieving the effect of improving the heat resistance of the copper clad laminate.
[0017] 2. The present invention prepares a tromethamine solution by first dissolving tromethamine in an ethanol solution, then uniformly dispersing halloysite nanotubes in the tromethamine solution, and then adding phytic acid for in-situ reaction to prepare a composite flame retardant material, so that the reaction product of tromethamine and phytic acid is coated on the surface of the halloysite nanotube. On the one hand, since the amino group of tromethamine reacts with the phosphate group of phytic acid to form a stable chemical bond, the surface properties of the halloysite nanotube can be adjusted and its compatibility with the modified adhesive can be improved. On the other hand, since the product of the reaction of tromethamine and phytic acid can promote the formation of a carbon layer and effectively isolate oxygen and heat, coating it on the surface of the halloysite nanotube can further improve the flame retardant properties of the halloysite nanotube. Therefore, after the composite flame retardant material is added to the modified adhesive, the flame retardant properties of the modified adhesive can be effectively improved, thereby ensuring the safety and reliability of the copper clad laminate.
[0018] 3. The present invention first uses bisphenol A dianhydride, diphenyl ether dianhydride, 2,4-toluene diisocyanate and isophorone diisocyanate as raw materials to react and prepare a base adhesive with good bonding performance, and then uses terminal hydroxyl polydimethylsiloxane to modify the base adhesive, and introduces hydrophobic groups into the base adhesive by reacting the terminal hydroxyl groups of the terminal hydroxyl polydimethylsiloxane with the polar groups of the base adhesive, thereby effectively reducing the water absorption of the base adhesive, preventing it from absorbing water and reducing the adhesion between the copper foil and the polyimide film, and achieving the effect of extending the service life of the copper clad laminate. DETAILED DESCRIPTION
[0019] The following is a detailed description of a high heat-resistant copper-clad laminate and its preparation process provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.
[0020] Example 1 A preparation process of a high heat-resistant copper-clad laminate comprises the following steps: Preparation of silicone-containing resin: Dissolve m-diethynylbenzene and methylphenyldichlorosilane in tetrahydrofuran at a solid-liquid ratio of 1g:20mL to obtain m-diethynylbenzene solution and methylphenyldichlorosilane solution for use; then add the m-diethynylbenzene solution to ethylmagnesium bromide, heat under reflux at 60°C for 2h under the protection of nitrogen, and naturally cool to room temperature to obtain intermediate A; then add methylphenyldichlorosilane solution to intermediate A, continue to heat under reflux at 60°C for 2h, and naturally cool to room temperature to obtain intermediate B, wherein ethylmagnesium bromide and m-diethynylbenzene solution are soluble in water; The volume ratio of the acetic acid-toluene solution and the methylphenyldichlorosilane solution is 1:1.8:1.9. Finally, the intermediate B is placed in an ice water bath at 3°C, and an acetic acid-toluene solution and a hydrochloric acid aqueous solution are added, and then transferred to a centrifuge for centrifugation, and the upper organic phase is separated and washed. After the solvent is removed by reduced pressure distillation, a silicon-containing resin is obtained, wherein the acetic acid-toluene solution is prepared by mixing acetic acid and toluene in a volume ratio of 1:4, and the molar ratio of acetic acid to m-diethynylbenzene is 2:1, the concentration of the hydrochloric acid aqueous solution is 10%, and the volume ratio of the hydrochloric acid aqueous solution to the acetic acid-toluene solution is 1:3; Preparation of modified silicone resin liquid: 10 parts of isosorbide bis(terephthalate), 1 part of bisphenol A and 16 parts of dibenzoate are added to a reactor, heated and stirred at 150°C for 8 minutes to obtain a mixed reaction liquid, then 0.01 parts of 4-dimethylaminopyridine are added to the mixed reaction liquid, and the mixture is heated at 150°C for 20 minutes, then the mixture is heated to 180°C, and vacuum distilled for 40 minutes to remove phenol, and then the mixture is heated to 250°C and heated for reaction for 2 hours to obtain a crude product, and then the crude product is dissolved in chloroform, and methanol is added for alcohol precipitation, and the mixture is centrifuged, washed and dried to obtain a modifier, and finally the modifier and the above 30 parts of silicon-containing resin are added to 55 parts of N,N-dimethylformamide, heated and stirred at 60°C to fully dissolve, and then N,N-dimethylformamide is removed by rotary evaporation to obtain a modified silicon-containing resin liquid; Preparation of modified glue: 34 parts of bisphenol A dianhydride and 45 parts of diphenyl ether dianhydride are added to 60 parts of N,N′-dimethylacetamide, heated at 70°C, stirred and mixed, and kept warm to obtain a mixed solution, and then 16 parts of 2,4-toluene diisocyanate and 21 parts of isophorone diisocyanate are added to the mixed solution, and after being kept warm and stirred for 1 hour, the temperature is raised to 110°C, and the stirring reaction is continued for 1 hour. After naturally cooling to room temperature, a base adhesive solution is obtained. Finally, 20 parts of terminal hydroxyl polydimethylsiloxane are added to the base adhesive solution, heated at 60°C, stirred and reacted for 2 hours, and naturally cooled to room temperature to obtain a modified adhesive solution; Preparation of composite flame retardant materials: Adding tromethamine to a 70% ethanol solution at a solid-liquid ratio of 1 g:10 mL, heating and stirring at 60° C. until completely dissolved, to obtain a tromethamine solution, then adding halloysite nanotubes to the tromethamine solution at a solid-liquid ratio of 1 g:30 mL, ultrasonically treating for 30 minutes, and uniformly dispersing to obtain a halloysite nanotube dispersion, finally adding phytic acid to the halloysite nanotube dispersion, heating and stirring at 60° C. for reaction for 2 hours, washing and drying the precipitate after centrifugal separation, to obtain a composite flame retardant material, wherein the molar ratio of phytic acid to tromethamine is 1:1.1; S1: Pretreatment of polyimide film The thermosetting polyimide film is placed in a 5% sodium hydroxide aqueous solution at 50°C, soaked for 3 minutes, taken out and dried to obtain a pretreated polyimide film; S2: Preparation of mixed glue solution 20 parts of the modified silicone-containing resin liquid, 45 parts of the modified adhesive liquid and 30 parts of the composite flame retardant material are stirred and mixed uniformly to obtain a mixed adhesive liquid; S3: Preparation of prepreg The mixed adhesive solution is applied on the surface of the pretreated polyimide film, and baked at 80°C and 130°C for 10 hours and 1 hour respectively to obtain a prepreg; S4: Hot Press Curing Several of the above-mentioned prepregs are stacked together, cut, and then covered with copper foil on one side or both sides. After heat-pressing and curing treatment, a high heat-resistant copper-clad laminate is obtained.
[0021] Example 2 A preparation process of a high heat-resistant copper-clad laminate comprises the following steps: Preparation of silicone-containing resin: Dissolve m-diethynylbenzene and methylphenyldichlorosilane in tetrahydrofuran at a solid-liquid ratio of 1g:25mL to obtain m-diethynylbenzene solution and methylphenyldichlorosilane solution for use. Then add the m-diethynylbenzene solution to ethylmagnesium bromide, heat under reflux at 65°C for 2.5h under the protection of nitrogen, and cool naturally to room temperature to obtain intermediate A. Subsequently, add methylphenyldichlorosilane solution to intermediate A, continue to heat under reflux at 65°C for 2.5h, and cool naturally to room temperature to obtain intermediate B, wherein ethylmagnesium bromide, m-diethynylbenzene and methylphenyldichlorosilane are soluble in water. The volume ratio of the benzene solution to the methylphenyldichlorosilane solution is 1:2:2.1. Finally, the intermediate B is placed in a 4°C ice water bath, and an acetic acid-toluene solution and a hydrochloric acid aqueous solution are added, and then transferred to a centrifuge for centrifugation, and then the upper organic phase is separated and washed. After the solvent is removed by reduced pressure distillation, a silicon-containing resin is obtained, wherein the acetic acid-toluene solution is prepared by mixing acetic acid and toluene in a volume ratio of 1:5, and the molar ratio of acetic acid to m-diethynylbenzene is 2.5:1, the concentration of the hydrochloric acid aqueous solution is 10%, and the volume ratio of the hydrochloric acid aqueous solution to the acetic acid-toluene solution is 1:4; Preparation of modified silicone resin liquid: 11 parts of isosorbide bis(terephthalate), 1.5 parts of bisphenol A and 18 parts of dibenzoate are added to a reactor, heated and stirred at 155°C for 9 minutes to obtain a mixed reaction liquid, then 0.02 parts of 4-dimethylaminopyridine is added to the mixed reaction liquid, and the mixture is heated at 155°C for 25 minutes, then the mixture is heated to 185°C, and vacuum distilled for 45 minutes to remove phenol, and then the mixture is heated to 260°C and heated for reaction for 2.5 hours to obtain a crude product, and then the crude product is dissolved in chloroform, and methanol is added for alcohol precipitation, and the mixture is centrifuged, washed and dried to obtain a modifier, and finally the modifier and the above 35 parts of the silicon-containing resin are added to 65 parts of N,N-dimethylformamide, heated and stirred at 65°C to fully dissolve, and then the N,N-dimethylformamide is removed by rotary evaporation to obtain a modified silicon-containing resin liquid; Preparation of modified glue: 38 parts of bisphenol A dianhydride and 47 parts of diphenyl ether dianhydride are added to 65 parts of N,N′-dimethylacetamide, heated and stirred at 75°C to obtain a mixed solution, and then 18 parts of 2,4-toluene diisocyanate and 22 parts of isophorone diisocyanate are added to the mixed solution, and after being heated and stirred for 1.5 hours, the temperature is raised to 115°C, and the reaction is continued by stirring for 1.5 hours. After naturally cooling to room temperature, a base adhesive solution is obtained. Finally, 25 parts of terminal hydroxyl polydimethylsiloxane are added to the base adhesive solution, heated and stirred at 70°C for 3 hours, and naturally cooled to room temperature to obtain a modified adhesive solution; Preparation of composite flame retardant materials: Adding tromethamine to a 70% ethanol solution at a solid-liquid ratio of 1 g:11 mL, heating and stirring at 65° C. until completely dissolved, to obtain a tromethamine solution, then adding halloysite nanotubes to the tromethamine solution at a solid-liquid ratio of 1 g:35 mL, ultrasonically treating for 35 minutes, and uniformly dispersing to obtain a halloysite nanotube dispersion, finally adding phytic acid to the halloysite nanotube dispersion, heating and stirring at 70° C. for reaction for 3 hours, washing and drying the precipitate after centrifugal separation, to obtain a composite flame retardant material, wherein the molar ratio of phytic acid to tromethamine is 1:1.2; S1: Pretreatment of polyimide film The thermosetting polyimide film is placed in a 5% sodium hydroxide aqueous solution at 55°C, soaked for 4 minutes, taken out and dried to obtain a pretreated polyimide film; S2: Preparation of mixed glue solution 25 parts of the modified silicone-containing resin liquid, 50 parts of the modified adhesive liquid and 35 parts of the composite flame retardant material are stirred and mixed uniformly to obtain a mixed adhesive liquid; S3: Preparation of prepreg The mixed adhesive solution is applied to the surface of the pretreated polyimide film, and baked at 85°C and 140°C for 11 hours and 1.5 hours, respectively, to obtain a prepreg; S4: Hot Press Curing Several of the above-mentioned prepregs are stacked together, cut, and then covered with copper foil on one side or both sides. After heat-pressing and curing treatment, a high heat-resistant copper-clad laminate is obtained.
[0022] Example 3 A preparation process of a high heat-resistant copper-clad laminate comprises the following steps: Preparation of silicone-containing resin: Dissolve m-diethynylbenzene and methylphenyldichlorosilane in tetrahydrofuran at a solid-liquid ratio of 1g:30mL to obtain m-diethynylbenzene solution and methylphenyldichlorosilane solution for use; then add the m-diethynylbenzene solution to ethylmagnesium bromide, heat under reflux at 70°C for 3h under the protection of nitrogen, and naturally cool to room temperature to obtain intermediate A; then add methylphenyldichlorosilane solution to intermediate A, continue to heat under reflux at 70°C for 3h, and naturally cool to room temperature to obtain intermediate B, wherein ethylmagnesium bromide and m-diethynylbenzene solution are soluble in water; The volume ratio of the acetic acid-toluene solution and the methylphenyldichlorosilane solution is 1:2.2:2.3. Finally, the intermediate B is placed in an ice water bath at 5°C, and an acetic acid-toluene solution and a hydrochloric acid aqueous solution are added, and then transferred to a centrifuge for centrifugation, and the upper organic phase is separated and washed. After the solvent is removed by reduced pressure distillation, a silicon-containing resin is obtained, wherein the acetic acid-toluene solution is prepared by mixing acetic acid and toluene in a volume ratio of 1:6, and the molar ratio of acetic acid to m-diethynylbenzene is 3:1, the concentration of the hydrochloric acid aqueous solution is 10%, and the volume ratio of the hydrochloric acid aqueous solution to the acetic acid-toluene solution is 1:5; Preparation of modified silicone resin liquid: 12 parts of isosorbide bis(terephthalate), 2 parts of bisphenol A and 20 parts of dibenzoate are added to a reactor, heated and stirred at 160°C for 10 minutes to obtain a mixed reaction liquid, then 0.03 parts of 4-dimethylaminopyridine is added to the mixed reaction liquid, and the mixture is heated at 160°C for 30 minutes, then the mixture is heated to 190°C, and vacuum distilled for 50 minutes to remove phenol, and then the mixture is heated to 270°C and heated for reaction for 3 hours to obtain a crude product, and then the crude product is dissolved in chloroform, and methanol is added for alcohol precipitation, and the mixture is centrifuged, washed and dried to obtain a modifier, and finally the modifier and the above 40 parts of silicon-containing resin are added to 75 parts of N,N-dimethylformamide, heated and stirred at 70°C to fully dissolve, and then N,N-dimethylformamide is removed by rotary evaporation to obtain a modified silicon-containing resin liquid; Preparation of modified glue: 42 parts of bisphenol A dianhydride and 50 parts of diphenyl ether dianhydride are added to 70 parts of N,N′-dimethylacetamide, heated at 80°C, stirred and mixed, and kept warm to obtain a mixed solution, and then 20 parts of 2,4-toluene diisocyanate and 23 parts of isophorone diisocyanate are added to the mixed solution, and after being kept warm and stirred for 2 hours, the temperature is raised to 120°C, and the stirring reaction is continued for 2 hours. After naturally cooling to room temperature, a base adhesive solution is obtained. Finally, 30 parts of terminal hydroxyl polydimethylsiloxane are added to the base adhesive solution, heated at 80°C, stirred and reacted for 4 hours, and naturally cooled to room temperature to obtain a modified adhesive solution; Preparation of composite flame retardant materials: Adding tromethamine to a 70% ethanol solution at a solid-liquid ratio of 1 g:12 mL, heating and stirring at 70°C until completely dissolved, to obtain a tromethamine solution, then adding halloysite nanotubes to the tromethamine solution at a solid-liquid ratio of 1 g:40 mL, ultrasonically treating for 40 minutes, and uniformly dispersing to obtain a halloysite nanotube dispersion, finally adding phytic acid to the halloysite nanotube dispersion, heating and stirring at 80°C for 4 hours, and after centrifugal separation, washing and drying the precipitate to obtain a composite flame retardant material, wherein the molar ratio of phytic acid to tromethamine is 1:1.3; S1: Pretreatment of polyimide film The thermosetting polyimide film is placed in a 5% sodium hydroxide aqueous solution at 60°C, soaked for 5 minutes, taken out and dried to obtain a pretreated polyimide film; S2: Preparation of mixed glue solution 30 parts of the modified silicone-containing resin liquid, 55 parts of the modified adhesive liquid and 40 parts of the composite flame retardant material are stirred and mixed uniformly to obtain a mixed adhesive liquid; S3: Preparation of prepreg The mixed adhesive solution is applied on the surface of the pretreated polyimide film, and baked at 90°C and 150°C for 12 hours and 2 hours respectively to obtain a prepreg; S4: Hot Press Curing Several of the above-mentioned prepregs are stacked together, cut, and then covered with copper foil on one side or both sides. After heat-pressing and curing treatment, a high heat-resistant copper-clad laminate is obtained.
[0023] Performance Test: 1. The heat resistance (solder immersion resistance, 288° C.) and peel strength of the high heat-resistant copper-clad laminates prepared in Examples 1-3 were tested according to GB / T4723-1992 standard. The results are shown in Table 1. 2. The flame retardant properties of the high heat-resistant copper-clad laminates prepared in Examples 1-3 were tested according to the GB / T2406.2 oxygen index method. The results are shown in Table 1. 3. The water absorption of the high heat-resistant copper clad laminates prepared in Examples 1-3 was tested according to IPC-TM-650 2.6.2.1. The results are shown in Table 1.
[0024] Table 1: Summary of performance test results of Examples 1-3
[0025] Comparative Example 1 The difference between this comparative example 1 and example 1 is that the modified silicone-containing resin liquid in the mixed glue liquid is removed, and then the performance test is carried out according to the performance test method in example 1, and the results are shown in Table 2 below.
[0026] Table 2: Comparative Example 1 and Example 1 Performance Test Results Comparison Table
[0027] As can be seen from Table 2, the copper clad laminate prepared in Comparative Example 1 without adding the modified silicone-containing resin liquid has a solder immersion resistance time of about 38 minutes in a 288°C solder liquid, which is lower than that in Example 1. It can be seen that the silicone-containing resin is prepared by first reacting m-diethynylbenzene and methylphenyldichlorosilane as raw materials, and then isosorbide bis(terephthalate), bisphenol A and dibenzoate as raw materials, and reacting under the catalysis of 4-dimethylaminopyridine to prepare the modifier. When the silicone-containing resin is modified by the modifier to prepare the modified silicone-containing resin, the modifier can improve the thermal conductivity of the silicone-containing resin, which is helpful for the uniform distribution of heat and further improves the heat resistance of the silicone-containing resin. Therefore, after the modified silicone-containing resin is added to the modified glue, the heat resistance of the modified glue can be effectively improved, thereby achieving the effect of improving the heat resistance of the copper clad laminate.
[0028] Comparative Example 2 The difference between this comparative example 2 and example 1 is that the composite flame retardant material in the mixed glue solution is removed, and then a performance test is performed according to the performance test method in example 1, and the results are shown in Table 3 below.
[0029] Comparative Example 3 The difference between this comparative example 3 and example 1 is that the composite flame retardant material in the mixed glue is replaced with an equal amount of halloysite nanotubes, and then a performance test is performed according to the performance test method in example 1, and the results are shown in Table 3 below.
[0030] Table 3: Comparative Example 2-3 and Example 1 Performance Test Results Comparison Table
[0031] As can be seen from Table 3, the limiting oxygen index of the copper clad laminate obtained in Comparative Example 2 when no composite flame retardant material is added is about 25.1%, while in Comparative Example 3, after the composite flame retardant material is replaced with an equal amount of halloysite nanotubes, the limiting oxygen index of the copper clad laminate obtained is about 30.4%, which is higher than Comparative Example 2, but still lower than Example 1. It can be seen that by first dissolving benzyl alcohol in an ethanol solution to prepare a benzyl alcohol solution, then uniformly dispersing the halloysite nanotubes in the benzyl alcohol solution, and then adding phytic acid for in-situ reaction to prepare a composite flame retardant material, the reaction product of benzyl alcohol and phytic acid contains Coated on the surface of the halloysite nanotube, on the one hand, since the amino group of benzyl alcohol reacts with the phosphate group of phytic acid to form a stable chemical bond, the surface properties of the halloysite nanotube can be adjusted and its compatibility with the modified adhesive solution can be improved; on the other hand, since the product of the reaction of benzyl alcohol and phytic acid can promote the formation of a carbon layer and effectively isolate oxygen and heat, coating it on the surface of the halloysite nanotube can further improve the flame retardant properties of the halloysite nanotube. Therefore, after the composite flame retardant material is added to the modified adhesive solution, the flame retardant properties of the modified adhesive solution can be effectively improved, thereby ensuring the safety and reliability of the copper clad laminate.
[0032] Comparative Example 4 The difference between this comparative example 4 and example 1 is that the modified adhesive solution in the mixed adhesive solution is removed, and then the performance test is carried out according to the performance test method in example 1, and the results are shown in Table 4 below.
[0033] Comparative Example 5 The difference between this comparative example 5 and example 1 is that the modified adhesive in the mixed adhesive is replaced with an equal amount of base adhesive, and then a performance test is performed according to the performance test method in example 1, and the results are shown in Table 4 below.
[0034] Table 4: Comparative Examples 4-5 and Example 1 Performance Test Results Comparison Table
[0035] As can be seen from Table 4, after the modified adhesive in the mixed adhesive is removed in Comparative Example 4, the peel strength of the copper clad laminate obtained is about 1.65 N / mm, which is lower than that in Example 1. It can be seen that the base adhesive with good bonding performance is first prepared by reacting bisphenol A dianhydride, diphenyl ether dianhydride, 2,4-toluene diisocyanate and isophorone diisocyanate as raw materials, and then coated on the surface of the polyimide film, which can effectively improve the bonding performance between the polyimide film and the copper foil; In Comparative Example 5, after the modified adhesive was replaced with an equal amount of the base adhesive, the water absorption rate of the prepared copper clad laminate was about 1.08%, which was higher than that in Example 1. It can be seen that by modifying the base adhesive with terminal hydroxyl polydimethylsiloxane, and introducing hydrophobic groups into the base adhesive through the reaction of the terminal hydroxyl groups of the terminal hydroxyl polydimethylsiloxane with the polar groups of the base adhesive, the water absorption rate of the base adhesive can be effectively reduced, and the water absorption can be prevented from reducing the adhesion between the copper foil and the polyimide film, thereby achieving the effect of extending the service life of the copper clad laminate.
[0036] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a high heat-resistant copper-clad laminate, characterized in that: The steps include: S1: Pretreatment of polyimide film, The thermosetting polyimide film is placed in a 5% sodium hydroxide aqueous solution at 50-60° C., and after being kept warm and soaked for 3-5 minutes, taken out and dried to obtain a pretreated polyimide film; S2: prepare mixed glue solution, The modified silicone-containing resin liquid, the modified adhesive liquid and the composite flame retardant material are stirred and mixed uniformly to obtain a mixed adhesive liquid; S3: Preparing a prepreg, The mixed adhesive is applied to the surface of the pretreated polyimide film, and baked at 80-90°C and 130-150°C for 10-12h and 1-2h, respectively, to obtain a prepreg; S4: hot pressing curing, Several prepregs are stacked together, cut, and then covered with copper foil on one or both sides, and subjected to heat-pressing curing to obtain a high heat-resistant copper-clad laminate; The mixed adhesive solution includes, by weight: 20-30 parts of modified silicone resin solution, 45-55 parts of modified adhesive solution and 30-40 parts of composite flame retardant material; The raw material components required for the modified silicone-containing resin liquid include, by weight: 10-12 parts of isosorbide bis(terephthalate), 1-2 parts of bisphenol A, 16-20 parts of dibenzoate, 0.01-0.03 parts of 4-dimethylaminopyridine, 30-40 parts of silicone-containing resin and 55-75 parts of N,N-dimethylformamide; The raw material components required for the modified adhesive solution include, by weight: 16-20 parts of 2,4-toluene diisocyanate, 21-23 parts of isophorone diisocyanate, 34-42 parts of bisphenol A dianhydride, 45-50 parts of diphenyl ether dianhydride, 20-30 parts of terminal hydroxyl polydimethylsiloxane and 60-70 parts of N,N′-dimethylacetamide.
2. The process for preparing a high heat-resistant copper-clad laminate according to claim 1, characterized in that: The preparation steps of the modified silicone-containing resin liquid are as follows: Add isosorbide bis(terephthalate), bisphenol A and dibenzoate into a reactor, heat and stir at 150-160° C. for 8-10 minutes to obtain a mixed reaction liquid; Add 4-dimethylaminopyridine to the mixed reaction liquid, continue heating at 150-160°C for 20-30 min, then raise the temperature to 180-190°C, distill under reduced pressure for 40-50 min to remove phenol, then raise the temperature to 250-270°C, and heat to react for 2-3 h to obtain a crude product; The crude product is dissolved in chloroform, and methanol is added for alcohol precipitation, and the modified agent is obtained by centrifugal separation, washing and drying; The above-mentioned modifier and silicon-containing resin are added to N,N-dimethylformamide, heated and stirred at 60-70° C. to fully dissolve, and then the N,N-dimethylformamide is removed by rotary evaporation to obtain a modified silicon-containing resin liquid.
3. The process for preparing a high heat-resistant copper-clad laminate according to claim 2, characterized in that: The preparation steps of silicone resin are as follows: Dissolve m-diethynylbenzene and methylphenyldichlorosilane in tetrahydrofuran at a solid-liquid ratio of 1 g: (20-30) mL to obtain a m-diethynylbenzene solution and a methylphenyldichlorosilane solution; The above m-diethynylbenzene solution was added to ethylmagnesium bromide, and the mixture was heated to reflux at 60-70°C for 2-3 hours under the protection of nitrogen, and then naturally cooled to room temperature to obtain intermediate A; Add the above-mentioned methylphenyldichlorosilane solution to the above-mentioned intermediate A, continue heating and reflux reaction at 60-70° C. for 2-3 hours, and naturally cool to room temperature to obtain intermediate B; The intermediate B is placed in an ice-water bath at 3-5°C, and acetic acid-toluene solution and hydrochloric acid aqueous solution are added, then transferred to a centrifuge for centrifugation, and the upper organic phase is separated and washed, and the solvent is removed by reduced pressure distillation to obtain a silicon-containing resin.
4. The process for preparing a high heat-resistant copper-clad laminate according to claim 1, characterized in that: The preparation steps of the modified glue solution are as follows: Add bisphenol A dianhydride and diphenyl ether dianhydride into N,N′-dimethylacetamide, heat and stir to mix at 70-80° C. and keep warm to obtain a mixed solution; Add 2,4-toluene diisocyanate and isophorone diisocyanate to the mixed solution, keep warm and stir for 1-2 hours, then raise the temperature to 110-120°C, continue stirring and reacting for 1-2 hours, and naturally cool to room temperature to obtain a matrix glue solution; Add terminal hydroxyl polydimethylsiloxane to the above-mentioned base adhesive solution, heat and stir at 60-80° C. for 2-4 hours, and naturally cool to room temperature to obtain a modified adhesive solution.
5. The process for preparing a high heat-resistant copper-clad laminate according to claim 1, characterized in that: The preparation steps of the composite flame retardant material are as follows: Add tromethamine to 70% ethanol solution at a solid-liquid ratio of 1 g: (10-12) mL, heat and stir at 60-70° C. until completely dissolved, to obtain a tromethamine solution; Add halloysite nanotubes to the above-mentioned tromethamine solution at a solid-liquid ratio of 1 g: (30-40) mL, perform ultrasonic treatment for 30-40 min, and obtain a halloysite nanotube dispersion after uniform dispersion; Add phytic acid to the halloysite nanotube dispersion, heat and stir at 60-80° C. for 2-4 hours, and wash and dry the precipitate after centrifugal separation to obtain a composite flame retardant material.
6. The process for preparing a high heat-resistant copper-clad laminate according to claim 3, characterized in that: The volume ratio of ethylmagnesium bromide, m-diethynylbenzene solution and methylphenyldichlorosilane solution is 1:(1.8-2.2):(1.9-2.3).
7. The process for preparing a high heat-resistant copper-clad laminate according to claim 3, characterized in that: The acetic acid-toluene solution is prepared by mixing acetic acid and toluene in a volume ratio of 1:(4-6), and the molar ratio of acetic acid to m-diethynylbenzene is (2-3):
1.
8. The process for preparing a high heat-resistant copper-clad laminate according to claim 3, characterized in that: The concentration of the hydrochloric acid aqueous solution is 10%, and the volume ratio of the hydrochloric acid aqueous solution to the acetic acid-toluene solution is 1:(3-5).
9. The process for preparing a high heat-resistant copper-clad laminate according to claim 5, characterized in that: The molar ratio of phytic acid to tromethamine is 1:(1.1-1.3).
10. A high heat-resistant copper-clad laminate, characterized in that: It is prepared by the preparation process of a high heat-resistant copper-clad laminate as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Styryl polysilicon phenylate resin as well as preparation method and application of styryl polysilicon phenylate resin
CN108148202A
Preparation method of concrete embedded steel bar glue with anti-seismic property
CN113201303A
High-strength acrylate modified organic silicon pressure-sensitive adhesive and preparation method thereof
CN116042104A
Insulating coating as well as preparation method and application thereof
CN116960271A
Ultraviolet curing adhesive and preparation method thereof
CN117070176A
Cited By
Preparation method of high-frequency flexible copper-clad plate
CN121038113A